Pengaruh Tingkat Suku Bunga Dan Nilai Tukar Terhadap Indeks Harga Properti Residensial (IHPR) di Indonesia Tahun 2002-2013 - Magdalena Magdalena (Ultima Management : Jurnal Ilmu Manajemen, 2015)
This study aimed to analyze the macroeconomic factors such as exchange rate and interest rate in effect on the market price of the property and real estate in Indonesia (IHPR) during the years 2002-2013. Through the application of e-views, the causal relationship was found in time series data. VAR analysis and Granger Causality Test did not find any relationship between SBI and IHPR. However SBI affects EXCHANGE positively, and EXCHANGE affects IHPR. Every 1 point weakening of IDR in the previous period, assuming the IDR in the two previous periods fixed, the IHPR in year-t will increase by 0.004003 points. If IDR in two previous periods depreciated by 1 point with the assumption that the IDR at the previous period remains, then IHPR in year-t will increase by 0.007219 points. Keywords: SBI interest rates, IDR exchange rates, price of property, VAR, Granger Causality Test